Complete the square for the following equation: 2x^2+6x-3=0

2x2+6x-3=0To begin, we need to make sure x2 is by itself, meaning that we divide the whole equation by 2. So from here we get (2x2+6x-3=0) / 2 = x2+3x-3/2=0. Now as we have got the x2 on its own, we can now fully complete the square by using: 2[(x+3/2)2-3/2 - ...] = 0. Now the ... stands for a value that has come about from completing the square. And the value is as simple as (-3/2)2 = 9/4. So the correct equation is 2[(x+3/2)2-3/2-9/4]=0. So the correct equation is 2[(x+3/2)2-15/4]=0. However, to finish the equation, we must multiply the entirety of it by 2, and then we have fully completed the square. So therefore we get 2(x+3/2)2-15/2=0.

Related Maths A Level answers

All answers ▸

What is the equation of a curve with gradient 4x^3 -7x + 3/2 which passes through the point (2,9)?


A stone, of mass m, falls vertically downwards under gravity through still water. At time t, the stone has speed v and it experiences a resistance force of magnitude lmv, where l is a constant.


Use the substitution u=cos(2x)to find ∫(cos(2x))^2 (sin(2x))^3dx


If a ball is dropped from 6m above the ground, how long does it take to hit the floor and what is its speed at impact (assuming air resistance is negligible)?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences